Moral Deliberations in Modern Cinema - Vaknin, Samuel, 1961-; Rangelovska, Lidija (Salt Lake City, UT : Project Gutenberg, 2005)
"Moral Deliberations in Modern Cinema" by Samuel Vaknin is a philosophical essay collection published in the early 21st century. The book delves into the ethical ambiguities and moral conflicts depicted in modern films, using various cinematic works as case studies to explore themes such as identity, agency, and moral responsibility. Each essay examines a different film, providing an in-depth analysis of the characters and storylines while bringing to light their moral implications. In this thought-provoking collection, Vaknin analyzes films like "The Talented Mr. Ripley," "The Truman Show," "The Matrix," and "Titanic," among others. He engages with complex questions surrounding identity, free will, and the nature of morality as portrayed in these narratives. For instance, he discusses the identity disturbances faced by characters like Tom Ripley and Dan Merrick, who grapple with their sense of self amid psychological disorders. Furthermore, he examines how films illustrate broader societal issues, such as capitalism's ethical dilemmas in "The Truman Show" and the moral responsibilities individuals have towards one another, highlighted through the layers of injustice seen in "Titanic." Through these analyses, Vaknin invites readers to reflect on their ethical beliefs and the impact of media on moral perceptions. (This is an automatically generated summary.)
Release date is 2005-07-01
Keywords: Motion pictures -- Reviews